2004
DOI: 10.1098/rspb.2003.2672
|View full text |Cite
|
Sign up to set email alerts
|

Sexual imprinting in human mate choice

Abstract: Animal and human studies have shown that individuals choose mates partly on the basis of similarity, a tendency referred to as homogamy. Several authors have suggested that a specific innate recognition mechanism, phenotypic matching, allows the organism to detect similar others by their resemblance to itself. However, several objections have been raised to this theory on both empirical and theoretical grounds. Here, we report that homogamy in humans is attained partly by sexual imprinting on the opposite-sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
129
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 37 publications
10
129
4
3
Order By: Relevance
“…A study that used computer-graphic image manipulation has shown a significant relationship between similarity of faces to subjects and the subjects' ratings of attractiveness of the faces (Penton-Voak et al 1999). In a set of studies on facial appearance, independent judges correctly matched long-term male and female partners at a significantly higher rate than expected by chance (Bereczkei et al 2002(Bereczkei et al , 2004. Several works suggest that genetic similarity within blood groups and major histocompatibility complex influences human attractiveness judgements and mate choice (Rushton 1989;Wedekind & Fü ri 1997;Roberts et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that used computer-graphic image manipulation has shown a significant relationship between similarity of faces to subjects and the subjects' ratings of attractiveness of the faces (Penton-Voak et al 1999). In a set of studies on facial appearance, independent judges correctly matched long-term male and female partners at a significantly higher rate than expected by chance (Bereczkei et al 2002(Bereczkei et al , 2004. Several works suggest that genetic similarity within blood groups and major histocompatibility complex influences human attractiveness judgements and mate choice (Rushton 1989;Wedekind & Fü ri 1997;Roberts et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Second, beyond measuring facial proportions, independent judges were asked to evaluate similarities among the subjects' mate and subjects' parents. As in our former experiments (Bereczkei et al 2002(Bereczkei et al , 2004, they looked at various sets of individual photographs and rated facial resemblance among them.…”
Section: Introductionmentioning
confidence: 99%
“…This form of learning occurs early in life. When sexual imprinting occurs, young learn about a parental phenotype as a model for their later preferences for mates (Kendrick et al 1998;ten Cate and Vos 1999;Bereczkei et al 2004;Verzijden and ten Cate 2007). This mechanism matches an individual's preference to the parental phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of previous research was mainly to reveal adult's bias towards unknown individuals who resemble family members and used a wide range of methods, including ratings of photographs by independent judges (BERECZKEI, GYURIS, KOVES and BERNATH 2002;BERECZKEI, GYURIS and WEISFELD 2004), facialmetrics (NOJO, IHARA, FURUSAWA, AKAMATSU and ISHIDA 2011;WISZEWSKA, PAW-LOWSKI and BOOTHROYD 2007), and face manipulation software (KOCSOR and BERECZKEI, submitted). Most of these studies were inspired by the theory of sexual imprinting (e.g., BERECZKEI et al 2002;BERECZKEI, GYURIS and WEISFELD 2004).…”
Section: Introductionmentioning
confidence: 99%